Cerebellar involvement in hallucinations may transcend clinical conditions and perceptual modalities. (October 2021) - Lawn, Timothy; ffytche, Dominic
Abstract: Our recent neuroimaging study identified structural differences in cerebellar subfields linked to cortical attentional networks in patients with eye disease or Parkinson's disease who experience visual hallucinations and a commentary on the study by Zorzi et al. provided additional evidence of functional cerebellar changes in Dementia with Lewy bodies. Here, we review evidence for cerebellar involvement in hallucinations across multiple clinical conditions and sensory modalities as well as examine its wider clinical and mechanistic implications. The combined structural and functional evidence is consistent with two models of cerebellar contribution to hallucination which differ in their implied direction of cause, effect and temporal sequence. Additionally, we contend that the relatively neuroanatomically localised nature of the cerebellum makes it particularly suited to identifying changes affecting distributed cortical networks using imaging techniques. As such, cerebellar subfield differences may offer value as candidate prognostic and predictive biomarkers as well as targets for neuromodulatory treatment across a range of clinical conditions.